A qualitative exploration of the priorities and experiences of children with Duchenne muscular dystrophy, their parents, and healthcare professionals around weight management. Issue 26 (18th December 2022) - Walker, Meaghan; Mistry, Bhavnita; Amin, Reshma; McAdam, Laura; Kalnins, Daina; Lui, Toni; McPherson, Amy C.
Abstract: Purpose: The quality and length of life for boys with Duchenne muscular dystrophy (DMD) has improved due to medical advancements, but obesity has emerged as and may pose a risk to their physical health. Clinical guidelines recommend attention to weight management, but healthcare professionals (HCPs) find implementing them in clinical care challenging. Little information is available about the perspectives of children with DMD and their families around weight management. This study explored the key priorities of children with DMD, their parents, and HCPs who treat them, around weight management. Methods: Qualitative, individual, semi-structured interviews were conducted and analyzed using a qualitative descriptive approach. Results: Participants included parents of children with DMD ( n = 13), children with DMD ( n = 10), and HCPs ( n = 14). Theme one: "Competing priorities between healthcare providers, parents, and boys" contained two sub-themes: (i) Body mechanics and function; and (ii) Psychosocial well-being. Theme two: "The realities of living with Duchenne's Muscular Dystrophy, " with subthemes: (i) Striving for normality; (ii) The trajectory of DMD; (iii) The labour associated with DMD. Conclusion: HCPs, parents, and boys have diverging worldviews around weight management, highlighting the importance of integrating the priorities of families into care, even when not aligned with guideline recommendations. IMPLICATIONS FOR REHABILITATION: HCPs must understand the competing priorities in the lives of children with DMD and their families when discussing weight, weight management, and lifestyle changes. Quality of life and living a "normal" life are prioritized by children and families over the surveillance and time demands of lifestyle routines recommended by clinicians for weight management. Weight management recommendations should be based upon the individual needs and priorities of the family.